(untitled) (University of Warwick Press, 2019)
Most, if not all advanced economies have suffered gravely from the 2008 global financial crisis. Growth, productivity, real income and consumption have plunged and inequality, and in some cases poverty, spiked. Some countries, like Germany and Australia, were better able to cope with the consequences but austerity has taken its toll even on the strongest economies. The UK is no exception and the more recent period of economic recovery might be halted or even reversed by the political, economic, and policy uncertainty created by the Brexit referendum. This uncertainty related risk to growth could be even greater if the UK leaves the economic and legal framework provided by the EU. This CAGE policy report offers proposals from different perspectives to answer the overarching question: What is the role of a government in a modern economy after the global financial crisis and the Brexit vote? We report on economic and social challenges in the UK and discuss potential policy responses for the government to consider. Foreword by: Lord O’Donnell of Clapham.